Preparation of minor ginsenosides C-K and C-Mx from protopanaxadiol ginsenosides of American ginseng leaves by a enzyme from Aspergillus sp.agl-84 strain. (April 2021) - Yue, Hanlei; Liu, Chunying; Han, Yuting; Zhuang, Ziyu; Yu, Hongshan; Wang, Zhiwei; Sun, Changkai; Im, Wan-Teak; Jin, Fengxie
Graphical abstract: Highlights: PPD-ginsenosides with 79% of Rb3 and Rd, separated from American ginseng leaves. Ginsenosidase type-I (75.2 kDa) was purified from Aspergillus sp.agl-84. Enzyme velocities of Rb3 and Rd were higher than that from other strains. 2.5% PPD-ginsenosides were reacted at 45 °C and pH 5.0 for 24 h by crude enzyme. 4.1 g C-K and 4. 2 g C-Mx were obtained from 20 g PPD-ginsenosides. Abstract: To improve utilization of American-ginseng-leaf ginsenosides, the PPD-ginsenosides from American-ginseng-leaves was reacted by a ginsenosidase type-I from Aspergillus sp.agl-84 to prepare minor ginsenosides C-K and C-Mx. PPD-ginsenosides, containing over 79 % of Rb3 and Rd, were separated from American-ginseng-leaves; the yield was 10.5 %. The molecular weight of ginsenosidase type-I from Aspergillus sp.agl-84 was approximately 75.2 kDa; Michaelis constants Km and Vmax were 14.8 mM and 58.6 mM/h for Rb3, 15.4 mM and 56.8 mM/h for Rd. The enzyme reaction velocities on 3- O -glucosides of Rb3 and Rd were higher than that of other Aspergillus strain ginsenosidase type-I to prove that the enzyme was more suitable for conversion of PPD-ginsenosides from American-ginseng-leaves into C-K and C-Mx. According to enzyme reaction dynamic, 2.5 % PPD-ginsenosides were reacted at 45 °C and pH 5.0 for 24 h by a crude ginsenosidase type-I from Aspergillus sp.agl-84 strain. Here, 4.1 g C-K and 4. 2 g C-Mx were obtained from 20 g PPD-ginsenosides separating from 190 g American-ginseng-leaves. C-K molar yield was 34.3 %, C-Mx molar yield was 29.0 %, the total molar yield was 63.3 %. Therefore, minor ginsenosides C-K and C-Mx were successfully prepared from PPD-ginsenosides of American-ginseng-leaves using crude enzyme from Aspergillus sp.agl-84 at low cost.